Assessing changes in reaction time following RAMP warm-up and short-term repeated volleyball specific exercise in young players - Ciesluk, K.; Sadowska, D.; Krzepota, J. (Sensors, 2025)
The assessment of the various skills of athletes is carried out in terms of their ability to perform sport-specific tasks. The cognitive abilities of the players have significance for their effectiveness. In volleyball, a player`s ability to react quickly appears to be crucial in responding to an opponent`s dynamic play. The aim of the study was to evaluate the changes in reaction time to light signals following warm-up and physical exercise. Eighteen volleyball players (15.58 ± 2.01 years) participated in the study. Four FITLIGHT TrainerTM discs were placed on the wall facing the participant to conduct the reaction time test. The participant`s task was to react as quickly as possible to the illuminated disc by touching it with the palm of their hand. The procedure was repeated five times: before the warm-up, after the warm-up, and after each of the three agility tests. Friedman`s ANOVA showed statistically significant differences in reaction time between the tests (Chi2 ANOVA = 61.23; p < 0.001). All tests performed after the warm-up according to the RAMP protocol showed statistically significantly better results than those before the warm-up (p = 0.05). At the same time, no differences were observed between the tests performed after successive agility tests. The results indicated that a well-chosen warm-up plays an important role in shortening the time of visual-motor reaction to a light stimulus (RT). Subsequent studies should be expanded to include other research groups and assess other parameters.